The role of patient portals for cancer patients: a systematic review of benefits, challenges, and opportunities - Puspitasari, Halfie Zaqiyah Gusti; Nuzulullail, Agung Subakti; Deli, Dwina Oktavia; Irawan, Dana Prayoga; Yogatama, Bagaskara (Universitas Airlangga, 2025)
Introduction: Cancer patients have a complex journey. Technological developments offer convenience in communicating and accessing health information. Cancer patient portals were developed to coordinate and integrate care by overcoming existing barriers. This study aims to explain the benefits, challenges, and opportunities of using patient portals in oncology services. Methods: The design of this study was a systematic review, with the source articles drawn from PubMed, ScienceDirect, ProQuest, EBSCOhost, and Scopus. Inclusion and exclusion criteria were used to screen articles with the PRISMA 2020 guidelines. A critical appraisal was conducted using the JBI Critical Appraisal Checklist 2020 and the MMAT 2018. Narrative descriptive approaches are used for data synthesis. Results: We screened 3,301 articles using inclusion, exclusion, and duplication criteria, resulting in 10 articles for analysis. Communication and care coordination (n=4) were among the main benefits of using patient portals. Perceived obstacles such as limited resources (n=2), socio-demographic challenges (n=3), and limited information sources (n=2) are still found. On the other hand, the use of patient portals creates opportunities to address information needs and provide assistance (n=1), increase security and privacy (n=1), and improve service efficiency (n=2). Conclusions: Patient portals play an essential role in improving coordination and engagement among cancer patients, despite ongoing challenges related to access and digital literacy. For nursing, these portals strengthen nurses' roles in education, coordination, and the use of evidence-based technology to improve the quality of care.